Efficacy of risankizumab in patients with moderate‐to‐severe plaque psoriasis by baseline demographics, disease characteristics and prior biologic therapy: an integrated analysis of the phase III UltIMMa‐1 and UltIMMa‐2 studies. (3rd July 2020) - Strober, B.; Menter, A.; Leonardi, C.; Gordon, K.; Lambert, J.; Puig, L.; Photowala, H.; Longcore, M.; Zhan, T.; Foley, P.
Abstract: Background: Risankizumab is a humanized IgG monoclonal antibody that selectively inhibits interleukin‐23 through binding the p19 subunit. In Phase 3 trials, risankizumab demonstrated superior efficacy compared with adalimumab and ustekinumab in patients with moderate‐to‐severe plaque psoriasis. Here, we evaluated the impact of baseline characteristics on efficacy of risankizumab compared with ustekinumab in patients with moderate‐to‐severe plaque psoriasis. Methods: This analysis included all patients initially randomized to risankizumab or ustekinumab from the replicate, double‐blinded, randomized, placebo‐controlled phase 3 trials, UltIMMa‐1 (NCT02684370) and UltIMMa‐2 (NCT02684357). Patients received either risankizumab (150 mg) or ustekinumab (weight‐based; 45 or 90 mg per label) at weeks 0, 4, 16, 28 and 40. Efficacy was assessed as the proportion of patients achieving ≥90% improvement in Psoriasis Area and Severity Index (PASI 90) at weeks 16 and 52 by baseline patient demographics, disease characteristics and prior biologic exposure. Mean per cent improvement in PASI was calculated by body weight and body mass index at week 52. Missing efficacy data were imputed as non‐responders for categorical variables and last observation carried forward for continuous variables. Logistic regression analyses assessed for interactions between treatment and five independent variables (age, sex, weight, baseline PASI score and presence of psoriatic arthritis) at both weeks 16 and 52. Results: Baseline patient demographics, disease characteristics and prior biologic exposure were similar between patients randomized to risankizumab ( n  = 598) and ustekinumab ( n  = 199). At weeks 16 and 52, risankizumab demonstrated superior efficacy compared with ustekinumab across these patient characteristics ( P  < 0.01). Logistic regression analyses demonstrated that risankizumab was superior to ustekinumab at weeks 16 and 52 in all models tested ( P  < 0.0001 for all). Conclusions: Risankizumab demonstrated consistent and superior efficacy compared with ustekinumab regardless of patient demographics, disease characteristics or prior biologic exposure.